2010
DOI: 10.1016/j.yhbeh.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Social dominance in male vasopressin 1b receptor knockout mice

Abstract: We have previously reported that mice with a targeted disruption of their vasopressin 1b receptor gene, Avpr1b, have mild impairments in social recognition and reduced aggression. The reductions in aggression are limited to social forms of aggression, i.e., maternal and inter-male aggression, while predatory aggression remains unaffected. To further clarify the role of the Avpr1b in the regulation of social behavior we first examined anxiety-like and depression-like behaviors in Avpr1b knockout (Avpr1b −/−) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Variants within AVPR1B have been linked to social behavior in humans and other mammals. As mentioned earlier, Avpr1b −/− mice show decreased aggression and altered dominance behavior (Caldwell et al, 2010; Pagani et al, 2015). Human studies including our results have linked AVPR1B to disorders with social components including bipolar type I, depression, autistic traits as measured by EQ, childhood aggression, COMD, suicidal attempts, prosociality, and emotional empathy (Dempster et al, 2007; Chakrabarti et al, 2009; Leszczynska-Rodziewicz et al, 2012; Zai et al, 2012; Szczepankiewicz et al, 2013; Luppino et al, 2014; Wu et al, 2015).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Variants within AVPR1B have been linked to social behavior in humans and other mammals. As mentioned earlier, Avpr1b −/− mice show decreased aggression and altered dominance behavior (Caldwell et al, 2010; Pagani et al, 2015). Human studies including our results have linked AVPR1B to disorders with social components including bipolar type I, depression, autistic traits as measured by EQ, childhood aggression, COMD, suicidal attempts, prosociality, and emotional empathy (Dempster et al, 2007; Chakrabarti et al, 2009; Leszczynska-Rodziewicz et al, 2012; Zai et al, 2012; Szczepankiewicz et al, 2013; Luppino et al, 2014; Wu et al, 2015).…”
Section: Discussionsupporting
confidence: 53%
“…Studies have shown that Avpr1b knockout mice display decreased ultrasonic vocalization in social situations throughout their lifespans, decreased aggression, and altered social behavior affiliated with dominance (Scattoni et al, 2008; Caldwell et al, 2010; Pagani et al, 2015). The relationship between Avpr1b and aggression was strengthened by the Pagani et al (2015) study, which showed the rescue of aggression by targeted expression of Avpr1b in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of behavioral response depends upon early social experience. The V1bR also has a role to play in modulating aggression in males (54). Aggressive behavior in females is not normally observed in response to AVP (55).…”
Section: Vasopressinmentioning
confidence: 99%
“…The AVP-ergic projections from the BNST and MeA to the lateral septum (LS) are also important for aggression and are strongly androgen-dependent, as surveyed by Caldwell et al [8]. Numerous studies suggest mediating functions of AVPR1B receptors in aggression [30] and indicate that the interconnecting 5-HT-ergic elements decrease AVPfacilitated aggression [31]. Furthermore, AVP is involved in affiliation such as pair bonding, or paternal or maternal care [8].…”
Section: Behavioral Consequences Of Avpmentioning
confidence: 99%